The Hidden Benefits of Being an Involved Father - Garret D. Evans; Kate Fogarty (EDIS)
Most people can agree that having an involved father has obvious benefits to children. Many of us have read newspapers or seen TV programs that talk about the clear benefits of fathers being involved in raising a child by providing love, support, and comfort. We can probably also agree that fathers are important because they help to teach children values and lessons in solving the problems they may face. Fathers also serve as role models in their childern's lives that affect how well they relate to peers and adults outside the home. This document is FCS2137, one of a series of the Family, Youth, and Community Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: December 1999. Revised: July 2005.